Hydrogen Production Simulation From Empty Palm Oil Bunches Using Aspen Plus - Sapari, Budiman; Hotman H. Simatupang; Isra Anwar; Muhammad Syukri Nur (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
A simulation model of biomass gasification for hydrogen production has been further developed using Aspen Plus. The model developed is based on Gibbs free energy minimization using the finite equilibrium method. The objective was to study the effect of important parameters such as gasification temperature, steam to biomass ratio and shift reaction temperature on hydrogen concentration. Simulations were conducted for palm empty bunch feedstock. The simulation results show that the main gas components in the synthetic gas are H₂, CO, CO₂, CH₄. Hydrogen gas increases with increasing temperature, hydrogen concentration increases from 22 kg/hour to 64 kg/hour but CH₄ concentration decreases from 50 kg/hour to 0 kg/hour with increasing temperature from 500-800˚C under 500 kg/hour steam flow rate operation.